Design of a microfluidic device for comprehensive spatial two‐dimensional liquid chromatography. Issue 7 (9th March 2015) - Wouters, Bert; De Vos, Jelle; Desmet, Gert; Terryn, Herman; Schoenmakers, Peter J.; Eeltink, Sebastiaan
<x xml:space="preserve">Abstract</x> This study discusses the design aspects for the construction of a microfluidic device for comprehensive spatial two‐dimensional liquid chromatography. In spatial two‐dimensional liquid chromatography each peak is characterized by its coordinates in the plane. After completing the first‐dimension separation all fractions are analyzed in parallel second‐dimension separations. Hence, spatial two‐dimensional liquid chromatography potentially provides much higher peak‐production rates than a coupled column multi‐dimensional liquid chromatography approach in which the second‐dimension analyses are performed sequentially. A chip for spatial two‐dimensional liquid chromatography has been manufactured from cyclic olefin copolymer and features a first‐dimension separation channel and 21 parallel second‐dimension separation channels oriented perpendicularly to the former. Compartmentalization of first‐ and second‐dimension developments by physical barriers allowed for a preferential flow path with a minimal dispersion into the second‐dimension separation channels. To generate a homogenous flow across all the parallel second‐dimension channels, a radially interconnected flow distributor containing two zones of diamond‐shaped pillars was integrated on‐chip. A methacrylate ester based monolithic stationary phase with optimized macroporous structure was created in situ in the confines of the microfluidic chip. In addition, the use of a photomask was explored to localize monolith formation in the parallel second‐dimension channels. Finally, to connect the spatial chip to the liquid chromatography instrument, connector ports were integrated allowing the use of Viper fittings. As an alternative, a chip holder with adjustable clasp locks was designed that allows the clamping force to be adjusted.